Exploring the underlying mechanisms of customers’ intention to adopt product recommendations from live streamers: A moderated mediation approach - Liping Zhang; Xueping Wu (PLoS ONE, 2025)
Live streaming has emerged as one of the indispensable channels for product information dissemination. Product recommendations from live streamers play an increasingly important role in customers’ purchasing decisions. Our study aims to understand the mechanism behind individuals’ intention to adopt product recommendations in live streaming. To that end, we implemented a moderated mediation model to test the direct and indirect effects of perceived value on customers’ intention to adopt product recommendations from live streamers, the mediating role of perceived credibility in the relationship between perceived value and adoption intention, the moderating role of sense of telepresence in the link between perceived value and perceived credibility, and the moderating role of self-identification in the association between perceived credibility and adoption intention. Results show that perceived credibility plays a partial intermediary role in the link between perceived value and adoption intention, sense of telepresence can positively predict perceived credibility but cannot significantly moderate the relationship between perceived value and adoption intention, and self-identification can positively buffer the association between perceived credibility and adoption intention, but negatively moderate the relationship between perceived value and adoption intention. This study advances theoretical research on product recommendations in the live-streaming context and provides practical inspiration for live streamers and managers of social commerce companies.